Metode Dakwah Ustaza Lasminora terhadap Pemahaman Keagamaan di Pengajian Rutin Jamaah Masjid Al-Fatah - Ardiansyah, Muhammad; Murdiati, Eni; Dewi, Emi Puspita (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
ABSTRACT: The thesis is entitled "Ustaza Lasminora's Method of Da'wah towards Religious Understanding in the Al-Fatah Mosque Congregational Regular Recitation". The type of research used is qualitative research. Data collection techniques include observation, interviews and documentation with data analysis techniques including data reduction, data presentation, drawing conclusions. The research results of Ustaza Lasminora's da'wah method on religious understanding at Al-Fatah Mosque Congregational Regular Recitations are by using the Al-Hikmah da'wah method: in which the congregation gets many lessons about life, one of which is by gaining an understanding of religious knowledge on an understanding that has been confused so far. Da'wah Mau'idzatatil Hasanah: carried out by providing religious knowledge that is beneficial to the congregation as well as Ustadza Lasminora including trustworthy leaders, increasing patience, perseverance and inviting the right path by guiding the congregation to discuss with each other or just exchanging ideas becomes a very important thing where things This can strengthen the ties of friendship and sympathy, and obtain happiness in this world and the hereafter. And da'wah mujaddalah: namely honesty and truth. Then da'wah is presented in a simple, simple and down-to-earth way that is close to the reality of the daily life of the congregation, so that in this way it can really be practiced in everyday life in understanding the issues of aqidah, sharia and morals.